Impact of detraining process experienced during the COVID-19 pandemic on the selected physical and motor features of football players - Korkmaz, Sezgin; Aslan, Cem Sinan; Eyuboğlu, Ender; Çelebi, Murat; Kır, Rıdvan; Karakulak, İzzet; Akyüz, Ömer; Özer, Uğur; Geri, Serdar (Progress in Nutrition, 2020)
Study Objectives: The purpose of this study was to examine the changes in the selected physical and physiological properties of football players in the long-term detraining stage during the pandemic period. Methods: In this study, 14 semi-professional football players (mean age: 22.21±3.29 years old and mean height: 177.86±5.35 cm) took part voluntarily. The participants had remained in detraining in the home environment for 89 days until the final measurements, following the decision of cessation of the leagues made by the Turkish Football Federation, except soft and irregular exercises they did with theirbody weight. The participants’ body composition characteristics, anaerobic performance, flexibility, and speed performance were measured. The descriptive statistics for numeric variables were expressed as mean±standard deviation. Since parametric test assumptions were provided as a result of examining the data acquired from the experimental subjects via the Shapiro-Wilk test, the repetitive measurements were evaluated using the “Paired-Sample t-test”. In addition, the mathematical differences between the two measurements were indicated with percentage. The results were evaluated at the confidence interval of 95% and the value p